Comparison of antioxidant activities from four species of piper - Muhamad Insanu; Lia Marliani; Nabila Pandu Dinilah (Pharmaciana, 2017)
Some species from Piper genus were known for traditional medicine and ornamental plant. Previous studies showed that Piper betle and Piper acre had antioxidant activities. But, the study of antioxidant activity from other species of Piper was still limited. Because of that, the purposes of this study were to determine the antioxidant activity, and total flavonoid content of Piper nigrum, Piper aduncum, Piper retrofractum, and Piper crocatum. Extraction was done by gradient maceration using n-hexane, ethyl acetate, and ethanol as solvents. The extracts were concentrated by rotary evaporator. Antioxidant activity was evaluated by DPPH (1,1-diphenyl-2-picrylhydrazyl) free scavenging method. Total flavonoid determination was done by colorimetry method using aluminum chloride (AlCl3) as a reagent. The result showed that the IC50 values of Piper nigrum, Piper aduncum, Piper retrofractum, and Piper crocatum were ranged between 58-1249 Î¼g/mL. The total flavonoid values of all extracts were between 1.4-8.3 mg QE/100 mg. The extract which had the strongest antioxidant activity was the ethanol extract of Piper nigrum with an IC50 value was Â 57.72 Î¼g/mL. The highest values of total flavonoid was showed by the ethanol extract of Piper aduncum which was 8.3 mg QE/100 mg extract.